Self-made material in physical education: Teacher perceptions of the use of an emerging pedagogical model before and during the COVID-19 pandemic. (February 2023) - Méndez-Giménez, Antonio; Carriedo, Alejandro; Fernandez-Rio, Javier; Cecchini, José-Antonio
The COVID-19 pandemic caused drastic changes in education, which had to adapt to changing scenarios (online, face-to-face, hybrid teaching). Within physical education (PE), strategies such as 'do not use or share equipment' were proposed to avoid infections. These strategies fit with an emerging pedagogical model called the Self-made Material Model (SMM), which involves students creating their own PE equipment. The objectives of the present study were: (a) to analyse PE teachers' beliefs about the use of self-made material in their classes, (b) to evaluate teachers' perceptions of the impact of the use of self-made material in PE lessons during the pandemic and (c) to examine gender/age differences. A quantitative, snowball research design was followed. The Self-made Material Questionnaire (Méndez-Giménez and Fernández-Río, 2011 ) comprising two scales (41 items) was adapted: Teachers' beliefs about the use of self-made material scale and Teachers' perceptions of the impact of self-made material usage during the pandemic scale. In total, 1093 in-service teachers (443 women, 40.5%; M = 41.39, SD = 9.54) from 13 Ibero-American countries participated. Descriptive statistics were calculated, Student's T test was conducted for comparisons by gender and one-way analysis of variance (ANOVA) was run for comparisons by age ranges. Overall, the scores were high, emphasising the potential to promote recycling and students' creativity and respect for the material. Women scored higher in items such as promoting interdisciplinarity, equality, attention to disability and education in values. In total, 833 (76.21%) teachers used self-made material during the pandemic and reported high levels of satisfaction, expectations of use, usefulness and profitability. No gender differences were found. In the COVID-19 era, the SMM is playing a relevant role as a meaningful framework and a helpful teaching methodology in different educational scenarios.